Application of chemical looping air separation for MILD oxy‐combustion in the supercritical power plant with CO2 capture. Issue 5 (8th August 2018) - Chen, Shiyi; Hu, Jun; Sun, Zhao; Xiang, Wenguo
Abstract: Chemical looping air separation (CLAS) is a novel and promising technology for oxygen production. This paper presents the application of CLAS to the supercritical power plant for MILD oxy‐combustion. Compared with the reference conventional supercritical power plant, the power generation efficiency of the CLAS integrated MILD oxy‐combustion plant is only reduced by about ~1.37% points at the baseline case. CO2 compression process imposes additional ~3.97% points efficiency penalty, which is inevitable to all of the CO2 capture technologies. The net power efficiency of the CLAS integrated MILD oxy‐combustion plant is ~37.37%. Even though a higher reduction reactor temperature could boost the power efficiency and a higher oxidization reactor temperature reversely decreases the power efficiency, the influence of reactor temperature is marginal. The performance of CLAS integrated MILD oxy‐combustion plant is not sensitive to excess CO2 and O2 ratio. Different oxygen carriers have different suitable operating region, but possess similar power efficiency. The carbon capture rate of the CLAS integrated MILD oxy‐combustion plant is up to ~100%, resulting in a virtually carbon‐free fossil power plant. Abstract : Chemical looping air separation is integrated with MILD oxy‐combustion. Net power efficiency of the plant is 37.37% including CO2 compression. Sensitivity analysis is conducted.